The design and development of a multimedia-assisted mastery learning courseware in learning of cellular respiration - Mohamed Adnan Khan, Fazzlijan; Masood, Mona (2013)
The study of cellular respiration is one of the most important in biology but often difficult subjects to teach at the high school, undergraduate or continuing education levels.This paper discusses the design and development of a Multimedia-assisted Mastery Learning Courseware (MMLC) by using a mastery learning strategy to enhance the learning of cellular respiration among Matriculation students.A courseware entitled ―Cellular Respiration‖ was systematically developed using mastery learning elements to assist students who had difficulties in mastering and acquiring the concept of the topic.The model for the instructional system design and the a combined theory of instruction are introduced as the macro and micro stages of developing the courseware.The findings of this study show that the courseware is well designed in terms of using mastery learning elements which goes through a series of systematic testing stages.In turn, it is highly anticipated that the creation of the MMLC, would be a viable alternative approach so that all students could capture, in a richer and more meaningful manner, the concepts of cellular respiration.